AN ANALYSIS OF THE ART ELEMENTS UTILIZED IN A WORKS OF ART - Thakur, Meenakshi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The visual imagery of each work of art has its own different structure in terms of line, colour and form. Artists takes inspiration from nature and depicts it in their work of art through their imagination they do take the help of art elements to portray their diverse creativity and imagination. Some use these art elements consciously; others may use them unconsciously. Art elements are what the foundation stones that create a composition of a painting combined with design principles, as they are considered to be the building blocks, which are used by everyone to create art. Although a work of art can be analyzed on multiple levels and in multiple contexts, a formal analysis is quite simply an analysis of the forms utilized in the works of art. Not all artists use all the available elements in their creations, many use a selected few or blend of elements and medium in harmony with their comfort and style. In this research paper I have emphasized on the basic meanings of art elements so that every art lover can understand and appreciate art around them.